Alternative therapies for dry eye disease. Issue 4 (July 2021) - Mittal, Rhiya; Patel, Sneh; Galor, Anat
Abstract : Purpose of review: Dry eye disease (DED) is a multifactorial disease affecting approximately 5–50% of individuals in various populations. Contributors to DED include, but are not limited to, lacrimal gland hypofunction, meibomian gland dysfunction (MGD), ocular surface inflammation, and corneal nerve dysfunction. Current DED treatments target some facets of the disease, such as ocular surface inflammation, but not all individuals experience adequate symptom relief. As such, this review focuses on alternative and adjunct approaches that are being explored to target underlying contributors to DED. Recent findings: Neuromodulation, stem cell treatments, and oral royal jelly have all been studied in individuals with DED and lacrimal gland hypofunction, with promising results. In individuals with MGD, devices that provide eyelid warming or intense pulsed light therapy may reduce DED symptoms and signs, as may topical Manuka honey. For those with ocular surface inflammation, naturally derived anti-inflammatory agents may be helpful, with the compound trehalose being farthest along in the process of investigation. Nerve growth factor, blood-derived products, corneal neurotization, and to a lesser degree, fatty acids have been studied in individuals with DED and neurotrophic keratitis (i.e. corneal nerve hyposensitivity). Various adjuvant therapies have been investigated in individuals with DED with neuropathic pain (i.e. corneal nerve hypersensitivity) including nerve blocks, neurostimulation, botulinum toxin, and acupuncture, although study numbers and design are generally weaker than for the other DED sub-types. Summary: Several alternatives and adjunct DED therapies are being investigated that target various aspects of disease. For many, more robust studies are required to assess their sustainability and applicability.